2016
DOI: 10.1097/mat.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Bypass with Low- Versus High-Priming Volume: Comparison of Inflammatory Responses in a Rat Model

Abstract: A cardiopulmonary bypass (CPB) can preserve life. However, interactions between blood and large artificial surfaces might help to provoke a series of chain reactions during CPB that result in the formation and release of numerous powerful inflammatory mediators including hormones and autacoids. We postulated that small CPB circuits with reduced priming volumes and less surface areas that come into contact with blood would attenuate systemic inflammatory responses by reducing the levels of cytokines and organ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As described recently, limiting the circuit volume also prevented the appearance of an excessive and early inflammatory response, thanks to a limited contact area between blood and the circuit components [ 19 ]. This strategy allowed us to achieve normo-volemic hemodilution with a hematocrit value of >20% for ECC maintenance, which is consistent with clinical observations and contributes to limited mortality and potential acute renal failure [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described recently, limiting the circuit volume also prevented the appearance of an excessive and early inflammatory response, thanks to a limited contact area between blood and the circuit components [ 19 ]. This strategy allowed us to achieve normo-volemic hemodilution with a hematocrit value of >20% for ECC maintenance, which is consistent with clinical observations and contributes to limited mortality and potential acute renal failure [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, although the level of another clinical index of end organ damage, LDH, increased over the course of CPB in protocol 1, and was not reduced by ghrelin in that experiment (Figure 1B ) we showed that an additional post-CPB dose of ghrelin after CPB greatly reduced LDH in protocol 3, to nearly sham group level. CPB has been shown many times, to induce inflammation that in turn leads to dysfunction in multiple organ systems, including the cardiovascular, pulmonary, hepatic, renal and central nervous systems (Chello et al, 2006 ; Gottesman and Wityk, 2006 ; Gottesman et al, 2008 ; Heusch et al, 2012 ; Fujii et al, 2015 , 2016 ). This increase in LDH with time is most likely attributable to haemolysis resulting from the shear forces associated with the action of the roller pump used in this study, as previously reported (Möhnle et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animals were housed 3 per cage under controlled conditions (12:12 h-light dark cycles) and were fed ad libitum with water and standard food pellets (Oriental Yeast Co., Ltd, Tokyo, Japan). The rat CPB was applied via venoarterial bypass and performed following Fujii et al ( 2015 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation